Bibliometric Analysis of Scholarly Publications on the Zika Virus, 1952–2016. Issue 2 (3rd April 2018) - Delwiche, Frances A.
ABSTRACT: The 2015–2016 epidemic in the Americas caused by the Zika Virus (ZIKV) triggered a dramatic increase in the number of scholarly publications on this topic. In an effort to understand and characterize this body of literature, a bibliometric study was conducted on all articles found in PubMed that were published on ZIKV between 1952 and 2016. Study parameters included publication date, source journal, subject and category of source journal, and country of first author. The data was frequency-ranked, enabling identification of the most highly productive journal titles, subject areas, and countries. The study concluded with a comparison between the number of opinion pieces versus research articles published on ZIKV and five other emerging infectious diseases. Results of the study will be of interest to students, researchers, and librarians and information science professionals, and will serve as a baseline for subsequent analyses.